School and Crime - Todd R. Jones; Ezra Karger (Institute of Labor Economics (IZA), 2023)
Criminal activity is seasonal, peaking in the summer and declining through the winter. We provide the first evidence that arrests of children and reported crimes involving children follow a different pattern: peaking during the school year and declining in the summer. We use a regression discontinuity design surrounding the exact start and end dates of the school year to show that this pattern is caused by school: children aged 10–17 are roughly 50% more likely to be involved in a reported crime during the beginning of the school year relative to the weeks before school begins. This sharp increase is driven by student-on-student crimes occurring in school and during school hours. We use the timing of these patterns and a seasonal adjustment to argue that school increases reported crime rates (and arrests) involving 10–17-year-old offenders by 47% (41%) annually relative to a counterfactual where crime rates follow typical seasonal patterns. School exacerbates preexisting sex-based and race-based inequality in reported crime and arrest rates, increasing both the Black-white and male-female gap in reported juvenile crime and arrest rates by more than 40%.
Keywords: I2; K4; 330; school; crime; academic calendar; regression discontinuity